Antracitos Calcinados em Indústria Carboquímica: Produção, Caracterização e Aplicações - Vasconcelos, Rodrigo Figueiredo (2021)
In this work, porous carbonaceous materials based on coal, anthracite and commercial activated carbon were characterized and applied on the removal of polycyclic aromatic hydrocarbons (PAHs) and naphthalene present in a contaminated water samples through